Malaysian Tualang honey and its immunomodulatory properties - Chua, Chong Kuan (2017)
Discoveries of antibiotic resistant pathogens and failure in some conventional modern cancer treatments have led to the re-evaluation of ancient therapeutic remedies such as honey. In recent years, Malaysian Tualang honey (MTH) had been proven scientifically to possess many beneficial properties such as antimicrobial, antioxidant, anticancer, anti-inflammatory and wound healing potential. However, little scientific evidence about its immunomodulatory property has been published, therefore this study aimed to investigate the immunomodulatory effect of MTH.